Investigation of thymoquinone stability in black seed oil alginate beads - Alkhatib, Hamzeh; Mohamed, Farahidah; Mohmad Sabere, Awis Sukarni; Akkawi, Muhammad Eid; Doolaanea, Abd Almonem (Association of Biotechnology and Pharmacy, 2020)
Thymoquinone (TQ) is the main active compound in black seed oil (BSO) which has unacceptable taste. Many reports confirmed that TQ has medical uses, but very few reports have documented its quantification or stability after formulation. In addition, stability of pure TQ under different conditions was studied to confirm that TQ was unstable in aqueous solutions, especially under alkaline environment. On the other hand, it is rarely to find reports about stability of TQ in BSO or BSO formulations. However, one of the most strongly used excipient in taste masking and improvement stability of the active compounds is alginate which can fabricated as beads in the presence of calcium ions.This study aimed to encapsulate BSO in alginate beads, and then to study stability of TQ in both forms of BSO and BSO-alginate beads.BSO-alginate beads were fabricated in 1% w/v calcium chloride bath. Concentration of BSO in the beads was 15% w/w. Aqueous solution of TQ, BSO, and BSO-alginate beads were packed in glass containers, well closed and stored at 40°±2°C /75±5% RH for 30 days. After specific time intervals (0, 15, and 30 days), the TQ content was analysed by using HPLC.The results indicated a poor stability of TQ in aqueous solution. Concentration of TQ in the aqueous solution was significantly (p0.05) decreased from 97.290.33 µg/mL at day 0 to 56.800.08 µg/mL at day 30. Moreover, concentration of TQ extracted from BSO showed a significant decreasing (p0.05) from 2.11±0.02% at day 0 to 1.95±0.005% at day 30. On the other hand, the stability of TQ in alginate beads containing BSO was highly improved (p0.05), (1.65±0.03% at day 0 and 1.58±0.04% at day 30). TQ in BSO may undergo some oxidation reaction during the period of storage in the stability chambers resulting in TQ degradation. On the other hand, alginate beads act a barrier against TQ oxidation, prolonging its shelf-life. This study suggests that BSO-alginate beads are stable in term of active principle and can be used as a source to provide TQ due to the unsuitability of aqueous solutions to formulate TQ.